The sacrifice of Sunshine Girl / 3. - McKenzie, Paige (Haunting of Sunshine girl, 2017)
"Is Sunshine Griffith who she thinks she is? Now that her luiseach powers are fully awakened, and having barely survived an abyss full of demons at the end of Book Two, Sunshine must figure out who--or what--has been organizing the forces of darkness against her. Thanks to her brainiac boyfriend, Nolan, they not only unearth that Sunshine's death would trigger a calamitous event, but that all civilization depends on her survival."--Amazon.com.